Bioethanol Production from Sugar Cane Syrup by Thermo-tolerant Yeast, Kluyveromyces marxianus DMKU3-1042, using Fed-batch and Repeated-batch Fermentation in a Nonsterile System - Pimpakan, Podchamarn; Yongmanitchai, Wichien; Limtong, Savitree (Agriculture and Natural Resources, 2012)
Ethanol production from sugar cane syrup was carried out to compare the efﬁ ciency of batch-, fed-batch and repeated-batch fermentation using Kluyveromyces marxianus DMKU3-1042. The sugar cane syrup medium contained 18% total sugar, 0.1% (NH4)2SO4, 0.1% KH2PO4, and 0.1% MgSO4.7H2O, with the pH adjusted to 4.5. Experiments were carried out in a 2.5 L jar fermenter at a controlled temperature of 35 °C and an agitation speed of 300 rpm without aeration. All experiments were carried out in a nonsterile system that resembled the process used in the bioethanol fermentation industry in Thailand. The ethanol concentration from batch fermentation was lowest among the three processes where 6.35% w/v was achieved in 72 hr resulting in an ethanol productivity of 0.88 g.L-1. hr-1 and the ethanol yield corresponded to 82.73% of the theoretical yield. For fed-batch fermentation, the exponential feeding scheme barely improved the ethanol yields while sigmoidal feeding gave a considerably higher ﬁ nal ethanol concentration reaching 7.42% w/v which was equivalent to ethanol productivity at 1.03 g.L-1.hr-1 and 90.40% of theoretical yield. In the repeated-batch experiment, a rather high ethanol concentration of 7.91% w/v at 72 hr was obtained in the ﬁ rst batch with ethanol productivity of 1.10 g.L-1.hr-1 and 93.40% of the theoretical yield. However, the ﬁ nal ethanol contents of the two successive batches were relatively low at 6.01% w/v and 6.66% w/v, respectively. The results from this research demonstrated that in Thailand, sugar cane syrup could be employed as an alternative renewable carbon source for ethanol production using sigmoidal fed-batch fermentation with an efﬁ cient thermotolerant yeast strain (Kluyveromyces marxianus DMKU3-1042).